Cotton and Man-made Textile Sector in India - A Curtain Raiser and Relevant Environment Issues - KUMAR, V.; PATIL, P. G.; SUNDARAMOORTHY, C. (Cotton Research Journal, 2021)
India is one of the largest producer, consumer and exporter of cotton in the world. In the last two decades coinciding with IX, X, XI and XII Five Year Plans (FYP) of India ending 2017, dramatic change in cotton scenario had been witnessed in the country. From a crop of subsistence, cotton has emerged as preferred commercial crop that is playing a key role in enhancing income of farmers and in national economy, especially after inroads of Bt cotton in 2002. Though globally man-made fibres have predominant share, in India cotton has maintained its dominance in production of lint, consumption of yarn/fibre, production of fabric, per capita cloth availability and to a fair extent in exports vis-a-vis man- made fibre/fabric. We examined available data of Indian textile sector to dispense away the narrative that cotton is being replaced by polyester. During 1997-02 (IX FYP) average cotton yarn (CY) consumption was 2659 M kg/yr, against 1693 M kg of man-made yarn/fibre (MMY). However, with massive availability of raw cotton and fibre due to wide spread use of Bt cotton, consumption of CY during 2012-2017(XII FYP) reached to 4907 M kg/yr and that of MMY just to 1894 M kg. Production of fabric showed a trend commensurate with consumption of yarn/fibre. The average export of cotton based textile items during IX FYP accounted for 62.7% of the total textile goods export. However, the share of cotton based textile exports dropped compared to man-made textile goods in later period. The ratio of cotton to man-made textile goods, for most of the parameters are tilted in favour of cotton, except for exports. As far environmental issues, studies carried out world over and discussed here project cotton in clear advantage over polyester in water footprints, carbon footprints and energy usage. It is only in the processing where water consumption of cotton is higher than polyester. Cotton has the distinction of being sole fibre which conserves more energy than it consumes in its production. Indian cotton is estimated to consume 125.75 M GJ and conserve 404.65 M GJ energy. It also has the distinction of being sole fibre which sequesters more carbon than it emits in its production. Cotton crop in India is estimated to sequester 27.392 M t CO2 against emission of 11.206 M t CO2. Sociologically, cotton affects the lives of millions of Indians. These unique properties of cotton have no match by any man-made or natural fibre.